INVESTIGATING THE INFLUENCE OF THE FOUR-SQUARE WRITING METHOD ON YEAR 8 STUDENTS’ NARRATIVE WRITING SKILLS IN ENGLISH AS a SECOND LANGUAGE PENGARUH METODE FOUR-SQUARE WRITING PADA KEMAMPUAN MENULIS NARATIF PADA SISWA KELAS 8 - JUWITA FERAWATI (LP2MTBM MAKARIOZ, 2019)
Writing a narrative is known as something difficult especially by junior high school students in English as a Second Language. The researcher discovered this problem while on teaching practicum. The use of the Four-Square Writing Method is a strategy to help students to write better and more confidently and communicate their feelings and ideas through writing. This research focuses on improving students’ narrative writing and motivation by using the Four-Square Writing Method. The research questions included: Does the use of the Four-Square Writing Method improve students’ narrative writing skills and influence their motivation in English in Grade 8? If so, how?The research methodology used was Classroom Action Research over three cycles. The sample was one classroom of 35 eight graders of a Junior Christian school near Jakarta.The results of the post-test, questionnaire, and interviews used in the study showed that by applying the Four-Square Writing Method, the students’ writing was improved. and the students felt more confident in expressing their ideas and thoughts through writing. Their narrative writing in particular improved through providing details and vivid language to describe the setting and character and also included some good ideas for the plot. Recommendations from this study include that all language teachers in Junior High School should be encouraged to use FSW Method as it does improve students writing skills and in so doing improves students motivation.